Methodological and ethical challenges in violence research - Fraga, S (2016)
Violence is a relevant public health issue. It is recognized as a sensitive topic to research and introduces challenges not usually found when dealing with other research topics. Researchers face a major challenge that is how to identify and measure violence as it occurs in the general population. This paper intends to discuss and raise awareness to some of the main methodological and ethical challenges related to violence research.